An infant formula toxicity and toxicokinetic feeding study on carrageenan in preweaning piglets with special attention to the immune system and gastrointestinal tract. (March 2015) - Weiner, M.L.; Ferguson, H.E.; Thorsrud, B.A.; Nelson, K.G.; Blakemore, W.R.; Zeigler, B.; Cameron, M.J.; Brant, A.; Cochrane, L.; Pellerin, M.; Mahadevan, B.
Highlights: Neonatal pigs fed infant formula with carrageenan (CGN) at doses of 2250 ppm for 28 days had no adverse effects. GIT evaluation with special stains and immunohistochemistry (IL-8, TNF-α) found no CGN effects. Immunophenotyping of blood cells and blood cytokine evaluations (IL-1β, IL-6, IL-8, TNF-α) found no effects of CGN. Analysis of plasma for CGN levels found no absorption at any dose. CGN was shown to be safe to neonatal pigs at a maximal feasible concentration (2250 ppm) or 430 mg/kg bw/day. Abstract: A toxicity/toxicokinetic swine-adapted infant formula feeding study was conducted in Domestic Yorkshire Crossbred Swine from lactation day 3 for 28 consecutive days during the preweaning period at carrageenan concentrations of 0, 300, 1000 and 2250 ppm under GLP guidelines. This study extends the observations in newborn baboons (McGill et al., 1977) to piglets and evaluates additional parameters: organ weights, clinical chemistry, special gastrointestinal tract stains (toluidine blue, Periodic Acid–Schiff), plasma levels of carrageenan; and evaluation of potential immune system effects. Using validated methods, immunophenotyping of blood cell types (lymphocytes, monocytes, B cells, helper T cells, cytotoxic T cells, mature T cells), sandwich immunoassays for blood cytokine evaluations (IL-6, IL-8, IL1β, TNF-α), and immunohistochemical staining of the gut for IL-8 and TNF-α were conducted. No treatment-related adverse effects at any carrageenan concentration were found on any parameter. Glucosuria in a few animals was not considered treatment-related. The high dose in this study, equivalent to ~430 mg/kg/day, provides an adequate margin of exposure for human infants, as affirmed by JECFA and supports the safe use of carrageenan for infants ages 0–12 weeks and older and infants with special medical needs.